Synthesis of ammonium aluminum oxalate from Bayer aluminum hydroxide - Lee, Hwa Young (ELSEVIER SCIENCE BV, 2011)
The synthesis of ammonium aluminum oxalate was performed using Bayer aluminum hydroxide as a raw material. For this aim, Bayer aluminum hydroxide of 99.7% purity was dissolved in oxalic acid to produce an aqueous aluminum solution. As a result, it was found that a mixing ratio of ethanol to Al solution exceeding 2:1 and a pH adjusted to greater than 8.0 should be employed in the synthesis of ammonium aluminum oxalate. From the chemical analysis of ammonium aluminum oxalate prepared in this work, the NH(4), Al and C content were found to be 14.5. 7.18 and 17.4%, respectively which are very close to the theoretical values of (NH(4))(3)Al(C(2)O(4))(3)3H(2)O. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: HIGH-PURITY ALUMINA; STRUCTURAL-CHARACTERIZATION; SOLUTION BEHAVIOR; AQUEOUS ALUMINUM; NANO ALUMINA; POWDER; PARTICLES; ROUTE; AGENT